2023
DOI: 10.5194/ejm-35-243-2023
|View full text |Cite
|
Sign up to set email alerts
|

A framework for quantitative in situ evaluation of coupled substitutions between H+ and trace elements in natural rutile

Abstract: Abstract. The coupling behaviour of H+ and trace elements in rutile has been studied using in situ polarised Fourier transform infrared (FTIR) spectroscopy and laser ablation inductively coupled plasma mass spectrometry (LA–ICP–MS) analysis. H2O contents in rutile can be precisely and accurately quantified from polarised FTIR measurements on single grains in situ. The benefits of this novel approach compared to traditional quantification methods are the preservation of textural context and heterogeneities of w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 64 publications
0
9
0
Order By: Relevance
“…Peak deconvolution is used to identify different defects contributing to the OH-bands of the FTIR signal. Lueder et al ( 2023 ) identified six different trace-element related H + -defects in natural rutile: three narrow bands at ~ 3278 cm −1 , ~ 3295 cm −1 , and ~ 3323 cm −1 related to Ti 3+ , Fe 3+ and Al 3+ , respectively and three wide bands at ~ 3345 cm −1 , ~ 3370 cm −1 , and ~ 3390 cm −1 , related to Mg 2+ , Fe 2+ , and Cr 2+ , respectively. Based on these observations we performed peak deconvolution on all measured spectra.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Peak deconvolution is used to identify different defects contributing to the OH-bands of the FTIR signal. Lueder et al ( 2023 ) identified six different trace-element related H + -defects in natural rutile: three narrow bands at ~ 3278 cm −1 , ~ 3295 cm −1 , and ~ 3323 cm −1 related to Ti 3+ , Fe 3+ and Al 3+ , respectively and three wide bands at ~ 3345 cm −1 , ~ 3370 cm −1 , and ~ 3390 cm −1 , related to Mg 2+ , Fe 2+ , and Cr 2+ , respectively. Based on these observations we performed peak deconvolution on all measured spectra.…”
Section: Resultsmentioning
confidence: 99%
“…We performed polarized transmission FTIR spectroscopy at the University of Bern, following the measurement protocol and quantification described in Lueder et al ( 2023 ). Selected grains were mapped to evaluate intra-grain variability of H 2 O contents and H + diffusion.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations